Filled dietary fluoride supplement prescriptions for Medicaid-enrolled children living in states with high and low water fluoridation coverage - Griffin, Susan O. (J Am Dent Assoc, 2019)
BACKGROUND. Although dietary fluoride (F) supplements (DFS) are recommended for children who use F-deficient drinking water, no studies have examined filled DFS prescriptions across multiple states to examine the dosage consistency with current recommendations or prescription length. METHODS. This sequential cross-sectional analysis used Medicaid claims data for children aged 0.5 through 16 years who in 2011 lived in the 6 states with the lowest and the highest fluoridation coverage (≤ 34% and ≥ 95% of the public water system population fluoridated, respectively). For 2011, the authors calculated the mean percentage of children with filled DFS prescriptions and the change since 2000 across states with high and low fluoridation coverage, the percentage of children with filled DFS prescriptions containing F dosage consistent with current recommendations, and filled DFS prescription length and cost across states. RESULTS. In states with high fluoridation coverage, the mean percentage of children with a filled prescription was < 1% in both years; in states with low fluoridation coverage, this value increased from 0.9% to 10.3%, the highest increase (16.4 percentage points) since 2000 among children aged 0.5 through 2 years. The average prescription length was 72 days. Across states, the mean costs per child prescribed supplements and per enrollee were $17.60 and $1.05, respectively. CONCLUSIONS AND PRACTICAL IMPLICATIONS. Filled prescriptions largely followed current recommendations but reached only a small percentage of children in low-coverage states. The short prescription length indicated limited exposure for caries prevention. Results from these states suggest more children could have longer exposure to the caries-preventive benefits of F at a similar cost with water fluoridation as with DFS.